Interactive english phonics learning for kindergarten consonant-vowel-consonant (CVC) word using augmented reality technology - Lay, Foong Yee (Universiti Malaysia Sarawak (UNIMAS), 2014)
Phonics is the relationships of letter and sounds that important for children to develop and improve their English reading skill. However, many children do not get effective and evidencebased reading instruction. The government kindergarten does not focus on phonics learning while the private kindergarten pays more attention to it. Therefore, the purpose of this study is to carry out reviews and studies on the suitable English phonics content, learning method. courseware development criteria, and Augmented Reality interaction method that is most suitable in developing interactive English Phonics Learning for Kindergarten Consonant-Vowel-Consonant (CVC) word using Augmented Reality Technology. Augmented Reality (AR) started applying in education in order to make learning more interesting and effective. AR is a technology that allows the physical images or object mixed with a virtual layer. The image marker based technique of Augmented Reality technology allows children to interact with virtual phonics content through physical manipulation. This interactive method provides a better learning experience for children. In order to achieve the objectives of this project, the approaches that defined in reviews and studies have been used in framework design. A prototype has been developed using the framework.